(untitled) (Journal of the College of Basic Education, 2022)
The aim of the experiment was to study the effect of the basic amalgamation treatment between caustic soda and ammonia on Chemical composition and laboratory digestion factor in cane and determining the best percentage of incorporation. included the experiment The first five treatments are the control treatment, the second treatment (5% of) NaoH, and the third treatment 2% + NaoH 3% (ammonia) and the fourth treatment 3% + NaoH 2% (ammonia) and the fifth treatment (5%) ammonia), and the results showed a highly significant increase in the amount of cellulose upon the chemical treatment (treatments